The Relevance Of Economic Policy In Khulafal Rasyidin And Modern Era - Kurniadi, Kurniadi; Mu'min, Muh. Dian Nur Alim; Amir, AM Nur Atma; Misbahuddin, Misbahuddin; Siradjuddin, Siradjuddin (Jurnal Ar-Ribh, 2023)
After the death of Rasulullah saw, the country's economic system, especially in economic matters, was taken over by the khulafaul Rashidun. There were four leading figures in this phase, namely Abu Bakar Assiddiq, Umar bin Khattab, Uthman bin Affan, and Ali bin Abi Talib. The caliphs carried out their government system based on the guidance of the Prophet Muhammad based on the Qur'an and Sunnah. The purpose of this study was to find out the policies among the caliphs in managing the country's economic problems, as well as the relevance of the economic system during the Khulafaul Rashidun era to modern times. This research is a "field research" using qualitative methods. The results of the study show that there are differences between the friends in implementing various economic policies both in terms of state revenues and the method of channeling or distributing state assets to solve economic problems. One of the influencing factors was the existence of new problems arising from the conditions, both in terms of revenue, regional and political, which were faced by each caliph in his government. Until the modern era, the Islamic economy continues to adapt to the conditions of the times so that the Islamic economy continues to exist in the future and become a compatible economic system.